Esophageal Foreign Body Extraction Marbles With Modified Metal Hook Tool - Larasati, Kinanti Putri; Larasati, Kinanti Putri; Juniati, Sri Herawati (Journal of Neonatal Surgery, 2025)
A 4-year-old boy presented with chief complaint of swallowing a marble 10 hours before being admitted to the hospital. Radiologic examination of the thorax revealed an opacity of metallic density, round-shaped with a smooth edge and diameter of approximately 1.3 cm projecting at the level of 6th-7th cervical vertebrae. Esophageal foreign bodies are usually removed using rigid esophagoscopy. However, foreign bodies that are hard, smooth or round in shape will be more difficult to treat. The tools prepared are modified hook with the hook tip curved to match the shape of the marble. Esophagoscopy was performed under general anesthesia, a marble foreign body was seen surrounded by edematous and hyperemic esophageal mucosa at cricopharynx area. The modification hook that has been prepared was inserted beyond the marble and pulled outward slowly but the marble fell into the hypopharynx. The hypopharynx and nasopharynx were evaluated until the marble was found in the nasopharyngeal area, then the marble was removed using Magill forcep.